Non-native language proficiency may influence the responsiveness of bilingual parents towards young children with autism: A short report. (January 2020) - Smith, Jodie; Bent, Catherine A; Green, Cherie C; Woollacott, Alexandra; Hudry, Kristelle
Background and aims: Although bilingualism is a common worldwide phenomenon, limited research has considered the experiences of children with autism growing up in bilingual environments. Here, we investigated the potential influence of parental bilingualism, and native vs. non-native language use, on responsiveness to children's communication attempts during parent–child interactions where the child had autism. Specifically, we investigated the amount of parent responses to child verbal communication ( frequency ) and the promptness of these responses ( temporal synchrony ). Methods: Participants were 22 monolingual and 20 bilingual parents and their children with autism aged 2–6 years, recruited from a multicultural, metropolitan city where English is the dominant language. Extending from our previous report on this sample, we identified the frequency and temporal synchrony of parent responses from filmed 10-minute free-play sessions. Monolingual parents were videoed during one free-play session in English. Bilingual parents were videoed during two free-play sessions; one in their native language and one in English. We compared the frequency and temporal synchrony of parental responses across monolingual and bilingual parent groups and, for bilingual parents, across native vs. non-native (English) language interaction samples. Finally, we examined how other measures of bilingual parents' non-native language proficiency were associated with interaction responsiveness measures. Results: When using their native language, bilingual parents demonstrated reduced frequency of responsiveness (even when controlling for opportunities provided by the child) and less temporal synchrony to child communication compared to English-speaking monolingual parents. Bilingual parents were also less frequently responsive (but not less temporally synchronous) during their native- compared to during their non-native (English) language interactions. Moreover, for bilingual parents, more frequent responsiveness to child communication bids when interacting in non-native English was associated with greater assessed English vocabulary knowledge. Conclusions: In this sample, use of non-native English did not appear to adversely affect how often, or how quickly, bilingual parents responded to their children's verbal communication bids. However, nor did we find evidence of a native-language advantage. Rather, during English-language interactions, when these bilingual parents were responsive towards their children, this was on par with rates and timing of responsiveness shown by English-speaking monolinguals. This may partly be explained by bilinguals' non-native language proficiency, and habitual use/personal dominance patterns. Implications: These data suggest no definitive drawback of non-native language use for synchronous responsiveness by bilingual parents interacting with young children with autism. However, our data also serve to highlight the complex, multifaceted nature of adult bilingualism, and indicate the need for more research – with large, well-characterised samples – to permit strong conclusions concerning how parental language-use choices may influence children's natural learning environments, including in the context of autism and developmental language impairments.